2017
DOI: 10.33549/physiolres.933385
|View full text |Cite
|
Sign up to set email alerts
|

Cooling-Evoked Hemodynamic Perturbations Facilitate Sympathetic Activity with Subsequent Myogenic Vascular Oscillations via Alpha2-Adrenergic Receptors

Abstract: This study extends our previous work by examining the effects of alpha2-adrenoceptors under cold stimulation involving the increase of myogenic vascular oscillations as increases of very-low-frequency and low-frequency of the blood pressure variability. Forty-eight adult male Sprague-Dawley rats were randomly divided into four groups: vehicle; yohimbine; hexamethonium+yohimbine; guanethidine+yohimbine. Systolic blood pressure, heart rate, power spectral analysis of spontaneous blood pressure and heart rate var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We speculate that pressor and tachycardia responses of SAD/PSD rats under CS are due to the synergic actions of several CS-elicited factors, for instance, adrenergic receptors, nitric oxide, sensory nerves, and non-neural pathways [7,10,11,34,35], which all might produce vasoconstriction, thereby increase SBP. Furthermore, baroreflex failure of SAD unmasks sympathetic inhibition on the heart, thereby increasing HR.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We speculate that pressor and tachycardia responses of SAD/PSD rats under CS are due to the synergic actions of several CS-elicited factors, for instance, adrenergic receptors, nitric oxide, sensory nerves, and non-neural pathways [7,10,11,34,35], which all might produce vasoconstriction, thereby increase SBP. Furthermore, baroreflex failure of SAD unmasks sympathetic inhibition on the heart, thereby increasing HR.…”
Section: Discussionmentioning
confidence: 98%
“…Sleep disturbances and aversive cold stress (CS) are cardiovascular risk factors [10][11][12], highly prevalent, and often happen together. In the past, we have demonstrated that paradoxical sleep deprivation (PSD) rats in nat-ural baseline (PreCS) result in sympathoexcitation and intensifying myogenic oscillations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation